RP-HPLC Method Development and Validation for Simultaneous Estimation of Clarithromycin and Paracetamol. (21st August 2013) - Gangishetty, Sadana; Verma, Surajpal
Abstract : The present work describes a simple, rapid, and reproducible reverse phase high performance liquid chromatography (RP-HPLC) method for the simultaneous estimation of clarithromycin (CLA) and paracetamol (PCM). C18 column (Kromasil ODS, 5 µm, 250 × 4.6 mm) and a mobile phase containing phosphate buffer (0.05 M) along with 1-octane sulphonic acid sodium salt monohydrate (0.005 M) adjusted to pH 3.2: acetonitrile (50 : 50 v/v) mixture was used for the separation and quantification. The flow rate was 1.0 mL/min and the eluents were detected by UV detector at 205 nm. The retention times were found to be 2.21 and 3.73 mins, respectively. The developed method was validated according to ICH guidelines Q2 (R1) and found to be linear within the range of 75–175 µg/mL for both drugs. The developed method was applied successfully for assay of clarithromycin and paracetamol in their combined in-house developed dosage forms and in vitro dissolution studies.